2008
DOI: 10.2131/jts.33.415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of trace metals in tobacco of local and imported cigarette brands used in Pakistan by spectrophotometer through microwave digestion

Abstract: -Uncontrolled exposure of active and passive smokers to trace metals causes increase in health risks. The primary objective of this study was to determine whether local and imported cigarette brands used in Pakistan, have elevated levels of metals or not. Six metals manganese (Mn), cobalt (Co), copper (Cu), cadmium (Cd), lead (Pb) and zinc (Zn) were determined in tobacco of twenty cigarette contamination chances and for complete digestion of analytes a microwave digester was used. The analytical results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
3
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 21 publications
3
13
3
9
Order By: Relevance
“…The mean levels of Cd were similar to those found by Ajab et al (2008), Stephens et al (2005), and Galazyn-Sidorezuk et al (2008). They reported mean levels of 0.50, 0.60, and 0.76 μg/g, respectively.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The mean levels of Cd were similar to those found by Ajab et al (2008), Stephens et al (2005), and Galazyn-Sidorezuk et al (2008). They reported mean levels of 0.50, 0.60, and 0.76 μg/g, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…These results disagree with those reported by Zulfiqar et al (2006) for Pakistani cigarettes, when no correlation between Pb and Cr, Ni and Pb, and Ni and Cr levels were detected. No significant correlations were observed either between the levels of Cd and another heavy metals, unlike the results found by Zulfiqar et al (2006) and Ajab et al (2008), who described positive correlations between Cd and Pb levels in Pakistani (r = 0.694) and in imported cigarettes commercialized in Pakistan (r = 0.543), respectively. Similarly, Galazyn-Sidorezuk et al (2008) also showed a positive correlation between levels of Cd and Pb (r = 0.414) in cigarettes produced in Poland.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…30 A fumaça do cigarro é uma mistura de cerca de 4.700 substâncias tóxicas diferentes, apresentando uma fase gasosa e outra particulada. A fase gasosa é composta, entre outros, por monóxido de carbono, amônia, cetonas, formaldeído, acetaldeído e acroleína.…”
Section: Tabelaunclassified
“…Its heavy metal-absorption related to soil type and other conditions of growth was previously inspected by several researchers [1,2].…”
Section: Introductionmentioning
confidence: 99%